Relationships between Methylobacteria and Glyphosate with Native and Invasive Plant Species: Implications for Restoration. Issue 1 (13th December 2011) - Irvine, Irina C.; Witter, Marti S.; Brigham, Christy A.; Martiny, Jennifer B. H.
<x xml:space="preserve">Abstract</x> After removing invasive plants, whether by herbicides or other means, typical restoration design focuses on rebuilding native plant communities while disregarding soil microbial communities. However, microbial–plant interactions are known to influence the relative success of native versus invasive plants. Therefore, the abundance and composition of soil microorganisms may affect restoration efforts. We assessed the effect of herbicide treatment on phytosymbiotic pink‐pigmented facultative methylotrophic (PPFM) bacteria and the potential consequences of native and invasive species establishment post‐herbicide treatment in the lab and in a coastal sage scrub (CSS)/grassland restoration site. Lab tests showed that 4% glyphosate reduced PPFM abundance. PPFM addition to seeds increased seedling length of a native plant (Artemisia californica) but not an invasive plant (Hirschfeldia incana). At the restoration site, methanol addition (a PPFM substrate) improved native bunchgrass (Nassella pulchra) germination and size by 35% over controls. In a separate multispecies field experiment, PPFM addition stimulated the germination of N. pulchra, but not that of three invasive species. Neither PPFM nor methanol addition strongly affected the growth of any plant species. Overall, these results are consistent with the hypothesis that PPFMs have a greater benefit to native than invasive species. Together, these experiments suggest that methanol or PPFM addition could be useful in improving CSS/grassland restorations. Future work should test PPFM effects on additional species and determine how these results vary under different environmental conditions.